2003
DOI: 10.1111/1467-6486.00357
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimensions of the Internationalization of Firms*

Abstract: The paper argues that there are two dimensions of internationalization: one which refers to the production activities of firms abroad and one which focuses on the corporate governance dimension of firms. While the first one is well known in the literature on internationalization, the financial dimension has not yet been addressed empirically. At the same time there are indicators that financial internationalization is gaining importance. Using a sample of the 100 largest German companies it shows that both dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
33

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 27 publications
1
71
0
33
Order By: Relevance
“…Measuring multinationality is a contested and largely unresolved issue in international business research (Hassel et al, 2003;Ramaswamy, Kroek, & Renforth, 1996;Sullivan, 1994;Verbeke & Brugman, 2009), with little consensus on which measure is best given equivocal conceptualization and inadequate measurement in empirical studies (e.g., Contractor, Kundu, & Hsu, 2003;Ruigrok & Wagner, 2003;Sullivan, 1994). The problem goes beyond consensus to one of form.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring multinationality is a contested and largely unresolved issue in international business research (Hassel et al, 2003;Ramaswamy, Kroek, & Renforth, 1996;Sullivan, 1994;Verbeke & Brugman, 2009), with little consensus on which measure is best given equivocal conceptualization and inadequate measurement in empirical studies (e.g., Contractor, Kundu, & Hsu, 2003;Ruigrok & Wagner, 2003;Sullivan, 1994). The problem goes beyond consensus to one of form.…”
Section: Methodsmentioning
confidence: 99%
“…In Germany, 80% of family firms have international activities and 53% derive more than 40% of their sales internationally (Calabrò, Rüsen, Bartels, & Müller, 2014). Multinationality, defined as the spread and diversity of international activities undertaken by a firm (Asmussen, Pedersen, & Petersen, 2007;Hassel, Höpner, Kurdelbusch, Rehder, & Zugehör, 2003;Hennart, 2007), is attractive to family firms because of the opportunities it presents to sustain family firms' long-term strategy for growth for both the business and the family (Brigham, Lumpkin, Payne, & Zachary, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the DOI level means that companies are progressing in the internationalization process and has an impact on the export performance of the companies (Pangarkar, 2008). When subanalyses of DOI elements are conducted, it would be observed that there is a correlation between the performance and the factors of FSTS (Riahi -Balkaoui, 1998, Nehrt, 1999, Ruigrok et al, 2007Loncan and Nique, 2010), FATA (Sullivan,1994;Ramaswamy et al, 1996;Nehrt, 1999;Kennelly and Lewis, 2001), PDIO (Conway and Swift, 2000;Evans et al, 2000;Loncan and Nique, 2010), TMIE (Sua'rez-Ortega and A'lamoVera, 2005), FETE (Contractor et al, 2003;Hassel et al, 2003;Chang, 2007;Greve et al, 2009;Nielsen, 2010;Zhang and Toppinen, 2011), OSTS (Sullivan,1994;Ramaswamy et al, 1996;Kennelly and Lewis, 2001). Several correlations such as S (Lu and Beamish, 2004), J and U (Contractor et al, 2003), reverse U (Elango and Sethi, 2007), positive linear, positive decreasing (López-Morales and Gómez-Casas, 2014) between DOI and performance have been established by various researchers.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Another gateway of change was the rise of institutional investors as shareholders of German companies, a result of both the international diversification of the assets of Anglo-American funds and the formation of domestic funds. These 'two dimensions of internationalization' (Hassel et al, 2003) resulted in the 'discovery' that German companies had shareholders. In multiple regression, around 62% of the variance in the shareholder orientation of large firms can be explained through exposure to international product market competition and share ownership by institutional investors (which also exposes companies to the market for corporate control; Höpner, 2001, pp.…”
Section: Shareholder Orientation and Industrial Relations In Germanymentioning
confidence: 99%